Numerical investigation of outdoor cooling airflow patterns and thermal behaviour in an open air-conditioned space - Mostafa Mohamed Reda Salaheldin Rashed; Esmail M. Elbialy; Essam E. Khalil; Samy M. Morcos (Cairo : Mostafa Mohamed Reda Salaheldin Rashed, 2015)
A computational fluid dynamics model is developed to examine the airflow characteristics of an outdoor air-conditioned space using air supply diffusers. This thesis is devoted for numerically investigating the effect of location and number of diffusers, adding glass borders, selecting entrance location according to upcoming wind direction. The main objective of this work is to investigate the influence of model aerodynamics parameters on improving the thermal comfort of occupants. As an input to the full-scale 3-D model, an air supplying diffuser model is developed to supply cooled air into the outdoor seating area. The present research considered diffusers type, velocity and angle as constant parameters and focused on studying the effect of changing different parameters involved in model aerodynamic
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Mechanical Power Engineering
Issued also as CD
Keywords: Numerical Investigation; Outdoor Cooling; Thermal Comfort